Efficacy of an anti-cancer strategy targeting SET in canine osteosarcoma - TSUJI, Shunya (J Vet Med Sci, 2019)
Osteosarcoma (OSA) is the most common bone tumor in dogs. Protein phosphatase 2A (PP2A), an evolutionary conserved serine/threonine protein phosphatase, is a crucial tumor suppressor. SET is a PP2A inhibitory protein that directly interacts with PP2A and suppresses its phosphatase activity. SET has been reported as a contributor of wide range of human and dog tumor malignancies. However, the role of SET in canine OSA (cOSA) remains unknown. In this study, we investigated the role of SET in cOSA by using 2 cOSA cell lines: POS (primary origin) and HM-POS (metastatic origin). Knockdown (KD) of SET expression was noted to slightly suppress POS cell proliferation only. Furthermore, SET KD effectively suppressed colony formation ability of both POS and HM-POS cells. SET KD was observed to repress ERK1/2, mTOR, E2F1, and NF-κB signaling in HM-POS cells, whereas it inhibited only ERK1/2 signaling in POS. Further, it was observed that SET-targeting drug, FTY720, exerted anti-cancer effects in both POS and HM-POS cells. Moreover, the drug also enhanced the anti-cancer effect of cisplatin. The data suggested that a combination therapy, based on SET targeting drugs and cisplatin, could be a potent strategy for cOSA.